Penerapan Model Pembelajaran Inkuiri Terbimbing dengan Teknik Scaffolding untuk Meningkatkan Penalaran Ilmiah Siswa pada Materi Fluida Statis - Erin Erliana Afsari; Muslim; Agus Danawan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Scientific reasoning plays a crucial role in addressing globalization and solving various problems. However, students’ scientific reasoning skills are often still relatively weak and need to be improved. This study aims to determine the improvement in students’ scientific reasoning following the implementation of a guided inquiry learning model with scaffolding techniques on the topic of static fluids, and to assess students’ responses to learning that employs this approach. This study employed a quantitative approach with a One-Group Pretest-Posttest Design. The sampling technique used was purposive sampling, with a sample size of 32 students from the same class. Students’ scientific reasoning was measured using a test instrument consisting of 12 two-tier multiple-choice questions. The research data were analyzed using the Wilcoxon test, N-Gain calculations, and Rosenthal’s “r” effect size calculations. The results indicated a significant difference between the pretest and posttest scores. The calculated N-Gain score was 0.73, indicating a high-level improvement in students’ scientific reasoning. This indicates that an overall improvement in students’ scientific reasoning, as well as improvements for each indicator, was observed following the implementation of this learning model. The effect size calculation yielded a value of 0.85, which falls into the “high” category. This indicates that the intervention was effective in improving students’ scientific reasoning skills. In addition, students’ responses to the learning process also showed positive results. Based on these findings, the guided inquiry model using scaffolding techniques can be considered an option for implementation in physics instruction and as an alternative solution for developing students’ scientific reasoning.